Normativity of Professional Morality and Metaethics - A. A. Morozov; S. V. Denisenko (Дискурс, 2020)
Introduction. The paper deals with the problem of justification of professional morality. The emphasis is placed on professional and ethical problems of the activity of employees of internal Affairs bodies. The purpose of this paper is to create a version of the justification of the normativity of professional morality (for example, the ethics of an employee of internal Affairs bodies), which combines the traditional sources of normativity and the possibility of metaethical discourse. The need for an updated understanding of normative and professional morals stems from the need for a new methodology for creating a professional and ethical standard for an employee of internal Affairs bodies.Methodology and sources. The paper offers a methodological justification of the professional morality of a law enforcement officer based on the ideas of K. Korsgaard and J. Thomson, who proposed in their works various options for justifying the normativity of morality. We proceed from the recognition that the professional and ethical standard, as well as its justification, is not the final version of our understanding of professional morality. Our approach to understanding them is based on the Tulmin’s principle of intellectual initiative, which allows us to rationally recreate existing constructs.Results and discussion. The translation of professional and ethical issues into the discourse of metaethics creates the prerequisites for gaining the credibility of the requirements of professional morality. Normative ethics as the basis of professional morality is in good agreement with the metaethical response to the problem of normativity, referred to as ‘‘voluntarism‘‘. However, the latter adds little to the reflexivity of our beliefs. The position called ‘‘call for autonomy‘‘ is much more convincing. It is based on the Kantian proposition that moral demands take on reality in the individual's own will. It is the main source of normativity. An important step that gives integrity to the normativity of professional morality is to overcome the absolutism of ethical statements. This is the analysis of normative judgments, taking into account their reference to the context of a particular field of activity.Conclusion. The convergence of the discourses of normative ethics and metaethics allows us to develop a justification of normativity, in which the formal description of the requirements of professional morality is combined with the internal ability of the individual to correlate his own actions and decisions with professional and ethical priorities.